Preventing sudden death in competitive athletes: an overview - Rossi, A.; Claiborne, T.; Fetter, J. (International Journal of Athletic Therapy & Training, 2018)
Sudden cardiac death (SCD) is the leading cause of sudden death in young athletes. It has been estimated that SCD occurs three times more often in athletes than in nonathletes and is defined as a sudden unexpected death due to a previously undiagnosed cardiac structural abnormality. The precise incidence of SCD is unclear, but various studies have estimated that 2-3% of the general population have some cardiovascular anomaly and that the SCD rate in athletes ranges from 1:50,000 to 1:200,000 athletes per year. According to the National Athletic Trainers` Association (NATA) position statement on preventing sudden death, a report from the National Collegiate Athletic Association stated that the SCD rate in student-athletes is slightly higher, at 1:43,000 per year.